The Impact Of Oil Revenues On The Path Of Reforms In Algeria: Whom To Blame Government Or People? - Hamzaoui, Ahlem (جامعة الوادي - University of Eloued, 2020)
Although oil income has contributed to a large extent to Algeria’s economic prosperity by providing the required financial resources for investment in other sectors, the country’s overall economic performance and development have never reached their full potential levels. Examining whether oil revenues did actually help fostering economic development in Algeria is at the heart of the investigation. Though oil’s revenues, reforms that had been taken were not at the expectations of people and wherever you go you find citizens unsatisfied about their living conditions and about the economic and social situation as a whole. In this context, the most important question that must be asked is who is the responsible for the actual situation, is it government or people?.
مقال
Keywords: .Algeria, Oil revenues, Reform, Government, People